EXAMINING THE LEVEL OF EMOTIONAL INTELLIGENCE AMONG SEMESTER ONE STUDENTS IN UNIVERSITI TEKNOLOGI MARA PAHANG - Hamdzah, Nor Lailatul Azilah; Syed Hassan, Syed Najmuddin; Hassan, Ruslan (Journal of Human Capital Development (JHCD), 2016)
Emotional intelligence is defined as the capacity to reason about emotions. An individual needs to have equilibrium between academic intelligence and emotional intelligence so that s/he will be able to face and take challenges in life in a healthy way. This paper presents a pilot study that looks into the level of emotional intelligence among in Universiti Teknologi MARA (UiTM) Pahang. 30 semester one students from various faculties in UiTM Pahang were randomly selected. Using Tapia’s Emotional Quotient Inventory as an instrument for data collection, the analysis indicates that, on the whole, the respondents only scored an average level of emotional intelligence. The findings also reveal low means score for sub-skills of emotional intelligence such as self-regulation and motivation. Such findings have very important pedagogical implications on inculcating and enhancing these students’ level of emotional intelligence abilities. KEY WORDS: emotional intelligence, Tapia’s Emotional Quotient Inventory, self-awareness, self-regulation, empathy, social skills, motivation